BACTERIAL INVOLVEMENT OF PNEUMONIA IN BURN UNIT OF DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2022-2023) - Rafif Marten Rabbani Dachlan; Lynda Hariani; Juniastuti (Universitas Airlangga, 2026)
Highlights: Pneumonia occurred in 19.35% of burn patients, predominantly in adults aged 16–60 years with a slight male predominance. Gram-negative bacteria, particularly Acinetobacter baumannii and Pseudomonas aeruginosa, were the main pathogens, indicating a high burden of nosocomial infection. Abstract: Introduction: Pneumonia in burn patients is an issue in burn injuries, requiring sufficient care and attention from treatment. Pneumonia is an infection that injures the lungs parenchyma, resulting in inflammation and bacteria playing a role in the increase of morbidity and mortality. This study aims to evaluate and describe the occurrence of pneumonia among burn patients. Methods: This retrospective observational study utilizes secondary data obtained from electronic medical records provided by Integrated Central Surgical Building (ICSB) Dr. Soetomo General Academic Hospital. EMR were collected from January 2022 to December 2023. The inclusion criteria were patients admitted with burn injuries and pneumonia. Samples excluded are those with incomplete variable, such as age, sex, comorbidities, length of stay, and causative pathogen. Results: A total of 124 patients were included in this study Pneumonia in Burn Patients in the burn units of Dr. Soetomo General Academic hospital were 24 (19.35%) patients, ages 16-60 were the most prominent age group. Males were slightly more likely to be affected with pneumonia, patients staying for more than 14 days (54%) were the largest group to be infected with pneumonia. Most common bacteria were Acinetobacter baumannii and Pseudomonas aeruginosa. Conclusion:Pneumonia occurred in 19% of burn patients, predominantly in adults aged 16–60 years with a slight male predominance, and was associated with prolonged hospital stay. Gram-negative bacteria, particularly Acinetobacter baumannii and Pseudomonas aeruginosa, were the main pathogens, highlighting pneumonia as a significant complication requiring early detection, infection control, and appropriate antimicrobial management.